2001
DOI: 10.1046/j.1365-3059.2001.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and relative humidity on conidial germination and viability, colonization and sporulation ofMonilinia fructigena

Abstract: Experiments were conducted to investigate the effects of temperature and relative humidity (RH) on the in vitro germination and viability of conidia of the apple brown rot fungus (Monilinia fructigena), and on colonization and sporulation on detached fruits by M. fructigena. Conidia only germinated under near-saturation humidity ($ 97% RH) and the rate of germination initially increased with temperature to a maximum at < 23±258C and then decreased. Conidia germinated rapidly ± more than 70% of viable conidia h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 22 publications
6
66
2
Order By: Relevance
“…The approximate value of equilibrium relative humidity (98 ± 1, 86.5 ± 1 and 75 ± 1%) inside the desiccators was controlled by means of saturated salt solutions: K 2 SO 4 (98%), KCL (86.5%), and NaCl (75%) (Xu et al, 2001). These pure salts were mixed in 1 l of distilled water and stirred until a saturated salt solution was obtained.…”
Section: Controlling Chamber Humiditymentioning
confidence: 99%
“…The approximate value of equilibrium relative humidity (98 ± 1, 86.5 ± 1 and 75 ± 1%) inside the desiccators was controlled by means of saturated salt solutions: K 2 SO 4 (98%), KCL (86.5%), and NaCl (75%) (Xu et al, 2001). These pure salts were mixed in 1 l of distilled water and stirred until a saturated salt solution was obtained.…”
Section: Controlling Chamber Humiditymentioning
confidence: 99%
“…Conidia of Monilinia species can survive dry conditions, especially under relatively low temperatures and high relative humidity (Xu et al, 2001). …”
Section: Dried Fruitmentioning
confidence: 99%
“…Insects were shown to be able to transport conidia from one fruit to another (Croxall et al, 1951;Lack, 1989) and they were the major wounding agents in pome fruit orchards acting as prerequisite factors for infection (Xu et al, 2001). Insects (nitidulid beetles, vinegar flies and honeybees) can be important vectors of M. fructicola during fruit ripening by carrying and depositing conidia to injuries caused by oriental fruit moth, peach twig borers, Mediterranean fruit flies, etc.…”
Section: Natural Meansmentioning
confidence: 99%
See 1 more Smart Citation
“…are also dependent on ambient temperature, relative humidity (RH), and water availability (water activity: a w ) (Luo et al, 2001;Tamm and Flückiger, 1993;Xu et al, 2001). Casals et al (2010) reported that more than 80% of viable conidia of M. fructicola and M. fructigena can germinate within 2 h and those of M. laxa can germinate within 4 h at 25°C and 0.99 a w on culture media.…”
Section: Introductionmentioning
confidence: 99%